Work ability index - Finnish Institute of Occupational Health, Helsinki; Jahkola, Antti; Tuomi, Kaija; Ilmarinen, Juhani (Helsinki, 1998)
"This booklet describes the work ability index, a method developed by the Finnish Institute of Occupational Health for providing an assessment of how well a worker is able to perform his or her work. The index is determined on the basis of answers to a series of questions which take into account the physical and mental demands of the work and the worker's health status and resources. The score calculated from the responses depicts the worker's own concept of his or her work ability. Other topics discussed: example of the determination of the index; reference values; follow-up measures."